Bremen und die atlantische Sklaverei - Hagedorn, Jasper Henning (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Using the example of the trading city of Bremen, this book’s innovative approach combines the analysis of multiple layers of German entanglement with Atlantic Slavery. This method expands the previous economic-historical perspective of scholarly studies. Bremen profited from the sale of goods necessary for the slave economy and from plantation ownership. The Bremen authorities protected Bremen’s slave profiteers out of economic and political interest on an international level, while at the same time committing themselves to the suppression of the slave trade in international treaties. Studies of discourse, legal practices, diplomacy and migration demonstrate the relevance and presence of Atlantic Slavery in politics, economics and society.